Analisis Pengaruh Marketing Complex, Customer Satisfaction, Customer Awareness Dan Promosi, Mempengaruhi Customer Trust Melalui Customer Loyality Sebagai Variabel Intervening Pada Konsumen Skintific Di Surabaya - Irwan Valentin; Oliandes Sondakh (Journal of Innovative and Creativity, 2026)
This research investigates the impact of marketing complex, customer satisfaction, customer awareness, and promotion on customer trust, with customer loyalty serving as an intervening variable. The study focuses on Skintific customers in Surabaya, a prominent skincare brand in Indonesia. In a competitive beauty industry, customer trust is identified as a key driver of customer loyalty, influencing both repeat purchases and brand recommendations. This study uses a quantitative approach, employing a causal research design with Structural Equation Modeling (SEM) to test the relationships among the variables. The results indicate that all aspects of marketing, including product quality, pricing strategies, distribution, and promotional activities, significantly affect customer satisfaction and awareness, which in turn influence customer trust. Furthermore, customer trust is found to positively affect customer loyalty. The research offers practical insights for companies, especially in the skincare industry, to refine their marketing strategies and enhance customer loyalty. These findings contribute to the theoretical literature on marketing and consumer behavior, specifically within the context of beauty and skincare industries in Indonesia.